Актуальні питання інформаційного забезпечення дослідницьких інфраструктур - Любчич, А. М.; Мамаєв, І. О. (НДІ правового забезпечення інноваційного розвитку НАПрН України; Право, 2022)
У науковій роботі дослідженні правові та організаційні питання збору та обігу даних в аспекті інформаційного забезпечення дослідницьких інфраструктур. В статті обґрунтована підвищена важливість обігу даних для ефективної роботи дослідницьких інфраструктур. Роботою визначено ряд правових перешкод. По-перше, проаналізовані питання, що виникають у зв’язку з авторським правом. Встановлено, що частина проблем викликана неузгодженістю правового регулювання цієї сфери у різних країнах. Розглянуто приклад німецького законодавства про авторське право. По-друге, розглянуті проблеми, що пов’язані з нормами про захист персональних даних і конфіденційність. У цьому аспекті наголошено на проблемних питаннях обробки персональних даних громадян ЄС, пов’язаних з Загальним регламентом про захист даних (GDPR) та іншими актами. По-третє, увага приділена неконкурентній поведінці розпорядників даних («Інтернет-гігантів»). Зазначено, що їхня поведінка у сфері обігу даних все частіше стає предметом контролю з боку антимонопольних органів європейських держав. В якості прикладу наведено досвід Німеччини. У цьому ж аспекті наголошено на необхідності юридичного розмежування персональних, неперсональних та «змішаних» даних. По-четверте, статтею розглянуто проблему міжнародного наукового співробітництва за єдиним узгодженим законодавством. Роботою визначено ряд організаційних перешкод, що заважають раціональному використанню зібраних даних. По-перше, питання недоступності даних у локальних системах, коли масиви цінних даних (такі як вимірювання, чи результати високовартісних досліджень) не можуть використовуватися науковою спільнотою в повній мірі. По-друге, питання невідповідності даних принципам FAIR (Findable, Accessible, Interoperable, Reusable) та значення цих принципів для ефективної дослідницької діяльності. По-третє, увага приділена важливості машинної обробки даних та проблемам, що з нею пов’язані. По-четверте, розглянуто проблему відсутності централізованої інфраструктури даних та обґрунтована важливість утворення подібної інфраструктури. Problem setting. The construction of an innovation society and ensuring the competitiveness of domestic science depends largely on the effective activity of research infrastructures. In turn, research infrastructures depend on their information support, as information is one of the most valuable resources in the modern world. Analysis of recent researches and publications. Innovative infrastructures were investigated in the works of such domestic scientists as S. V. Hlibko, I. V. Podrez-Riapolova and others. Research infrastructure was considered by N. M. Vnukova, O. V. Holovashchenko, V. P. Kokhan. H. P. Klimova investigated the issue of knowledge transfer in innovative infrastructures. Among the foreign scientists who have studied research infrastructure, you can mention M. Stührenberg, O. Schonefeld, A. Witt, F. Giladi and others. Target of research. The purpose of the article is to identify legal and organizational obstacles that interfere with the rational use of data, as well as to determine the means of eliminating them for establishing effective information support of research infrastructures. Article’s main body. Effective activity of research infrastructures is possible solely if their information support is available. In turn, obtaining access to information and its circulation are faced with a number of legal and organizational problems. Legal problems include: 1) copyright issues that are quite inconsistent in different countries and requires special approaches; 2) issues of protection of personal data; 3) issues of behavior of Internet giants; 4) issues of international scientific cooperation under a single agreed legislation. Organizational problems include: 1) the issue of irrational use of data through their localization, stagnation and «dying» in one place; 2) issues of implementation of fair-principles of data management; 3) questions of standardization of data for the machine processing; 4) issues of construction of centralized data infrastructure. Conclusions and prospects for the development. Researchers who work with personal data of EU citizens should pay attention to the peculiarities of protection of personal data defined by General Data Protection Regulation, Regulation No. 1725/2018 and other acts. The specifics of copyright rules at the level of individual national legislation should also be taken into account. One of the significant obstacles to the free receipt of large and useful arrays of information is the behavior of Internet giants, which complicate its free circulation on the basis of “protection of personal data”. In connection with this domestic legislators, it is advisable to draw a clear boundary between «personal», «non -personal», «mixed», «anonymized» and «pseudonymized» data. For more efficient development of national research infrastructures, Ukraine should increase international cooperation, in particular on ERIC projects and integration into the European Research Area. In order to prevent irrational use of information, it is necessary to promote FAIR-principles (Findable, Accessible, Interoperable, Reusable) of data management and pay attention to the standardization of scientific data for their processing machine. It is advisable to build a centralized data infrastructure, which will be able to ensure the practical execution of these condemnations and rationalizes the accumulation and circulation of data.
Keywords: дослідницькі інфраструктури; інформаційне забезпечення; обіг даних; персональні дані; неперсональні дані; локалізація даних; інфраструктури даних; принципи FAIR; research infrastructure; information support; data circulation; personal data; non-personal data; data localization; data infrastructure; FAIR principles